European network of trainees in obstetrics and gynaecology: experiences from the 2016 exchange programme in Turin, Italy - Eismann, Sabine; Schott, Sarah (Archives of gynecology and obstetrics, 2017)
Introduction: The European Network of Trainees in Obstetrics and Gynaecology (ENTOG) is an organization representing trainees from 30 European member countries. Together with the European Board and College of Obstetrics and Gynaecology (EBCOG), it seeks to achieve the highest possible standards of training and consequently to improve the quality of medical care in the field of gynaecology and obstetrics. Every year, the ENTOG council meets and holds a scientific meeting in a different European country. To coincide with this, the host country arranges an exchange, to which each member country can send two trainees. This exchange allows trainees to gain insight into both daily clinical work and the structure of the health care system. Methods: This article reports the experiences of participants in the May 2016 ENTOG exchange to Turin, Italy. The aim is to outline differences in training between Germany and Italy as well as some striking differences with other European countries. Perspective: The participants’ personal benefit from this unique experience was not only to get familiar with the Italian trainee programme and health care system, but also to exchange experiences among representatives from other European countries and build up a young gynaecological network within Europe.